Microstructural Evolution and Oxidation Resistance of Fe-30Ni-15Cr Alloy for Internal Combustion Engine Valves Under Long-Term High-Temperature Exposure and Heat Treatment - Yuguo Tu; Xueshan Xiao; Zhiyuan Zhu; Linzhen Zhou (Metals)
Iron–nickel-based superalloy is an ideal substitute for the expensive Inconel 625 and Inconel 751 alloys. To elucidate the evolution of the microstructure and properties of Ni30 alloy under different thermal treatment conditions, a systematic study was conducted on the microstructural transformation of the alloy’s strengthening γ′ phase following solution treatment and aging, as well prolonged exposure at 750 °C, and the oxidation behavior of the Ni30 alloy was examined. During prolonged thermal exposure, grain growth occurs mainly in the initial stage, and after 200 h, the prolonged exposure time leads to a significant coarsening of γ′ precipitates, whose area fraction increases by more than 10 times compared to their unaged state. After 100 h of aging, the alloy reaches a peak tensile strength of 1270 MPa and a yield strength of 820 MPa; after 2000 h, the alloy maintains a relatively high strength with a slight decrease in ductility. The oxidation kinetic curve of Ni30 alloy follows the quasi-parabolic oxidation law at 750 °C, and its oxidation rate is consistently lower than 0.1 g·m−2·h−1 throughout the whole oxidation process, which indicates that it has excellent oxidation resistance. The external oxide layer of Ni30 alloy shows a bilayered structure, and no obvious surface porosity or flaking of oxidation products were observed throughout the high-temperature oxidation test. This study not only contributes to the improvement of material properties, but also promotes innovation and development in the field of high-temperature engineering applications that will help to meet the increasingly stringent requirements of high-temperature working environments.